2020
DOI: 10.31223/osf.io/8vy6j
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Toward stable, general machine-learned models of the atmospheric chemical system

Abstract: Atmospheric chemistry models—used as components in models that simulate air pollution and climate change—are computationally expensive. Previous studies have shown that machine-learned atmospheric chemical solvers can be orders of magnitude faster than traditional integration methods but tend to suffer from numerical instability. Here, we present a modeling framework that reduces error accumulation compared to previous work while maintaining computational efficiency. Our approach is novel in that it: 1) uses a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 23 publications
0
23
1
Order By: Relevance
“…Figure 4 shows the error statistics for surface ozone when using the different ML solvers. None of the ML solvers show runaway error growth, unlike in previous studies (Keller & Evans, 2019; Kelp et al., 2020), which we attribute to the relatively low dimensionality of the Super‐Fast mechanism boosted by the use of the encoder/decoder to further reduce dimensionality.…”
Section: Resultscontrasting
confidence: 74%
See 4 more Smart Citations
“…Figure 4 shows the error statistics for surface ozone when using the different ML solvers. None of the ML solvers show runaway error growth, unlike in previous studies (Keller & Evans, 2019; Kelp et al., 2020), which we attribute to the relatively low dimensionality of the Super‐Fast mechanism boosted by the use of the encoder/decoder to further reduce dimensionality.…”
Section: Resultscontrasting
confidence: 74%
“…Kelp et al. (2020) found that a cost function that equally prioritizes all species is significantly less accurate than one that is specialized toward a single species of interest. Here, we create 12 separate ML solvers prioritizing each of the output species individually, all with the same 20 input variables listed from above.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations